The Role of Internal Communication in Infusing Corporate Values and Delivering Brand Promise: Singapore Airlines' Experience - CHONG, Mark (Institutional Knowledge at Singapore Management University, 2007)
Most studies on corporate branding and image have focused on the influence of external communication such as advertising and public relations. Less attention has been paid to the strategic role that internal communication and training can play. This study examines the internal communication and training functions at Singapore Airlines û one of the world's best international airlines û and how it is used strategically to enable cabin crew and ground staff to live its corporate values and consistently deliver on its brand promise of being 'a great way to fly'. It shows that internal communication and training should be treated as the 'first frontier' in the battle for the customer: when it is founded on strong corporate values, internal communication and training can help transform key employees such as cabin crew into 'walking embodiments' of the core values, and key touch points into opportunities for fulfilling the brand promise.